DIALEKTIKA TAFSIR DAN KEMAJUAN PENGETAHUAN DALAM TRANSPLANTASI ORGAN BABI PADA MANUSIA - Nurmansyah, Ihsan (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2020)
The advancement of knowledge and technology presents its own challenges to Muslims’ socio-religious life. One of them is the progress in the medical field regarding organ transplants of animals to humans. Religious problems arise when animals used in transplantation are those that are deemed unlawful (haram) by Islamic texts. On the one hand, organ transplants provide benefits for humanity, but on the other, donors of transplants are unlawful animals. This paper examines the lawfulness of using the body parts of pigs, whose unlawfulness is stated in many verses of the Qur'an. This study uses a contextual interpretation introduced by Abdullah Saeed. Based on contextual considerations, this study concludes that QS. al-Baqarah: 173, QS. al-Maidah: 3, QS. al-Anam: 145 and QS. an-Nahl: 115 prohibit pork for consumption. The commentators of the Qur’an have differences of opinion concerning the uses of pigs beyond consumption. This paper suggests that using the body parts of pigs is legitimate. This is reinforced by QS. al-Baqarah: 173 which explains an emergency context. Pigs do not belong to the category of najis ‘aini, which allows it to be transplanted into the human body. However, some conditions need to be fulfilled for transplantation. The transplantation permitted if these is not rise risk of further to harm and a recommendation from the doctor about the patient's condition.